2017
DOI: 10.1007/s11606-017-4122-y
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Public Disclosure of Industry Payments to Physicians on Patient Trust: A Randomized Experiment

Abstract: Disclosure of industry payments to physicians affected perceptions of individual physician honesty and fidelity, but not perceptions of competence. Disclosure did not affect trust ratings for the medical profession or the pharmaceutical and medical device industry. ClinicalTrials.gov identifier: NCT02179632 ( https://clinicaltrials.gov/ct2/show/NCT02179632 ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 38 publications
0
47
0
Order By: Relevance
“…However, one factor that has been shown to influence patient opinion is their perception of physicians' conflicts of interest, especially sponsorships from for-profit entities. 3 An inverse relationship exists between how much funding a physician is perceived to have received from industry and how high a trust rating patients assign to him/her. 3 Public media scrutiny has influenced this decline in trust.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one factor that has been shown to influence patient opinion is their perception of physicians' conflicts of interest, especially sponsorships from for-profit entities. 3 An inverse relationship exists between how much funding a physician is perceived to have received from industry and how high a trust rating patients assign to him/her. 3 Public media scrutiny has influenced this decline in trust.…”
Section: Introductionmentioning
confidence: 99%
“…3 An inverse relationship exists between how much funding a physician is perceived to have received from industry and how high a trust rating patients assign to him/her. 3 Public media scrutiny has influenced this decline in trust. A 2012 article in The Washington Post told the story of the diabetes drug Avandia (rosiglitazone).…”
Section: Introductionmentioning
confidence: 99%
“…Findings from survey and experimental studies on the relationship between patient trust and disclosure of industry ties have been mixed. Some studies 23 , 24 found that patients report higher levels of trust in physicians who disclose their industry relationships, while other studies 25 , 26 , 27 , 28 demonstrated lower levels of patient trust when physician financial conflicts of interest are disclosed.…”
Section: Introductionmentioning
confidence: 99%
“…The authors chose ProPublica's website and divided participants into four study arms to view physicians who received no payment, low payments, or high payments from industry, or physicians who provided no disclosure. 3 Only 278 English-speaking adults participated and were given the names of senior male physicians practicing internal medicine in Massachusetts. Only 19 participants found their own doctors listed on the disclosure website.…”
mentioning
confidence: 99%
“…Additionally, there were no differences between disclosure and no disclosure arms for any trust dimensions for the medical profession or industry. 3 The Physician Payments Sunshine Act mandates public disclosure of all industry payments to physicians, and has resulted in greater scrutiny of industry's relationship with physicians; however, payments to nurse practitioners and physician assistants are not covered. 4 Despite several limitations, including small sample size and limited availability of data within the ProPublica website, this study does add limited value to the growing body of literature on payment disclosures by physicians in various specialties.…”
mentioning
confidence: 99%